2023
DOI: 10.1111/ejn.16034
|View full text |Cite
|
Sign up to set email alerts
|

Neurophysiological indices of face processing in people with psychosis and their siblings: An event‐related potential study

Abstract: People with schizophrenia experience difficulties with social interactions. One contributor to these social deficits is dysfunction in processing facial features and facial emotional expressions. However, it is not known whether face processing deficits are evident in those with other psychotic disorders or in those genetically at‐risk for psychosis (i.e., first‐degree relatives of those with psychosis). We assessed event‐related potentials (ERPs) during a facial and emotion processing task in 100 people with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 56 publications
(71 reference statements)
0
2
0
Order By: Relevance
“…These findings converge with a recent N170 study from our laboratory that found evidence for a face effect deficit, but not an emotion effect deficit, in participants with psychotic disorders. 44 The study had several limitations. First, our building and face images were not matched on low-level visual features (eg, luminance, complexity, and saturation), which may alter the N170 face effect.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These findings converge with a recent N170 study from our laboratory that found evidence for a face effect deficit, but not an emotion effect deficit, in participants with psychotic disorders. 44 The study had several limitations. First, our building and face images were not matched on low-level visual features (eg, luminance, complexity, and saturation), which may alter the N170 face effect.…”
Section: Discussionmentioning
confidence: 99%
“…The ERP task was modified from previous studies 29,43,44 (Figure 1). The stimulus set included face and building images (Supplementary Section S1.2).…”
Section: Erp Taskmentioning
confidence: 99%